Analisis wacana bahasa perundingan Nabi Yusuf a.s. dalam penyelesaian konflik - Kasmawati, Zakaria (2022)
Language is considered the main foundation in studies on negotiation as language is used as a means for reconciling souls in conflict. Although there are many studies on the negotiation of discourse on the narration of the Qur'an, mainly from Surah Yusuf, however, the study is only descriptive based on a limited study of linguistic stature in terms of grammatical structure in a limited unit of verses. The study focuses less on the characteristics of language used by negotiators and its relationship to social processes that can be worked on through critical discourse analysis methodologies. This causes the understanding and interpretation of the narrative discourse of the Qur'an to experience a narrowing of meaning, thus narrowing the scope of the philosophy of language that can be examined through the study of semiosis. Thus, this study was conducted to examine the negotiating language of Prophet Yusuf a.s. through three objectives, namely to identify the characteristics of the negotatiation language of Prophet Yusuf a.s. in resolving intrapersonal and interpersonal conflicts, explains the discursive practices practiced by Prophet Yusuf a.s. in the discourse of his negotiation and analyze the dimension of compassion in the social process of the discourse of Prophet Yusuf a.s through his negotiation practices. This study is a qualitative study that employs data collection techniques in the nature of document analysis. A discourse analysis framework on the text of the Qur’an was utilized through the al-Zuhailīy Tafsir Model, Fairclough Three Dimensional Discourse Analysis, and Wodak Discourse Historical Approach in addition to several major theories from Arabic linguistics and theories from the West as a complement. From the analysis, it is concluded that the negotiating practice of Prophet Yusuf a.s. was formed from a problem-solution pattern. This practice is seen through the internal analysis of the text, i.e. the characteristics of the text and discursive practices. The features of the text begin with the determination of topics and themes that factor into lexical identification and style of negotiation language. From the analysis of discursive practice, this framework is envisioned from the way discourse is processed through details on discourse structure, discourse strategies as well as the discourse intertextuality and interdiscursivity. External analysis of the text in turn utilizes the dimension of courtesy as a practice of negotiation that exhibits the quality of negotiation based on the awareness that every action and speech is in the observation and evaluation of Allah s.w.t. The combination of language and social studies from the field of religious discourse analysis can further expand the exploration of the Qur'an, especially in providing solutions to the problems of the ummah.